INTEGRATION OF AIRBORNE TOPO-BATHYMETRY LIDAR DATA USING 3-DIMENSIONAL TRANSFORMATION METHOD - Utomo, Sepki
There are two Airborne Topo-Bathymetry LIDAR sensors, namely topographic and bathymetric sensors. On the ground, both sensors can record objects properly. However, in marine areas, topographic sensors can only acquire the surface of the water, in contrast to bathymetric sensors, which can acquire up to the seabed. Thus, there are differences between the two datasets such as resolution, precision, and accuracy, which are challenges in integrating topo-bathymetric data. Another challenge is the lack of data overlap between the two sensors, which creates a gap in the data. This research solves this challenge by using 3D conformal transformation methods, namely Bursa-Wolf and Molodensky-Badekas. Moreover, no studies are showing the results of using these two methods in integrating topo-bathymetric data. Other researchers who integrated topo-bathymetric data did not use this method. The determination of the allied points needed in data integration is obtained by using vectorize buildings and point to point methods on objects on land, considering that topographic sensors cannot acquire objects on the seabed. This study compares the results of the two methods of integration and the determination of common points. The results show that the Bursa-Wolf and Molodensky-Badekas methods can be used to integrate topo-bathymetric data as indicated by the change in the position of the bathymetric sensor towards the topographic sensor regardless of the method of determining the common point. Based on RMSE, the best-allied point method is the point to point.